2017
DOI: 10.1038/s41598-017-11274-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of 5′,6′-epoxyeicosatrienoic acid binding to and activation of TRPV4 channel

Abstract: TRPV4 cation channel activation by cytochrome P450-mediated derivatives of arachidonic acid (AA), epoxyeicosatrienoic acids (EETs), constitute a major mechanisms of endothelium-derived vasodilatation. Besides, TRPV4 mechano/osmosensitivity depends on phospholipase A2 (PLA2) activation and subsequent production of AA and EETs. However, the lack of evidence for a direct interaction of EETs with TRPV4 together with claims of EET-independent mechanical activation of TRPV4 has cast doubts on the validity of this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 69 publications
1
46
0
Order By: Relevance
“…; Berna‐Erro et al . ). The differences in TRPV4 expression in cells that form the inner and outer BRB (MVECs and HCECs) are consistent with the heterogeneity of TRPV4 signalling across dissimilar vascular beds (Maishan et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Berna‐Erro et al . ). The differences in TRPV4 expression in cells that form the inner and outer BRB (MVECs and HCECs) are consistent with the heterogeneity of TRPV4 signalling across dissimilar vascular beds (Maishan et al .…”
Section: Discussionmentioning
confidence: 97%
“…Such localized indirect activation is proposed to cause highly compartmentalized TRPV4-mediated Ca 2+ signaling at focal adhesions and facilitates downstream activation of additional β 1 -integrins (integrin-to-integrin signaling) and leads to cell reorientation (40,41). Moreover, several studies have shown that TRPV4 activation in response to osmotic or mechanical stress depends on formation of intracellular mechanomessengers, like lipid metabolites as arachidonic acid and its derivative 5 ′ ,6 ′epoxyeicosatrienoic acid, and PIP 2 (21,(42)(43)(44)(45). Additionally, calmodulin as a classical second messenger binds to TRPV4 and mediates Ca 2+ influx by conformational change and dissociation of its N-and C-terminus (20).…”
Section: Mechanotrpv4mentioning
confidence: 99%
“…Although the synthetic agonist 4␣-PDD activates TRPV4 by directly binding to its TM3 and TM4 segments in a ligand-like manner (38), earlier studies indicate that AA-induced TRPV4 activation involves metabolism of AA by cytochrome P450 into 5,6-epoxyeicosatrienoic acid (5,6-EET) (34,35,39). A recent study has further proposed a potential 5,6-EET-binding site in TRPV4, which is formed by residues from the TM2-TM3 linker, TM4, and TM4-TM5 linker (65). However, other studies indicate that TRPV4 can also be activated by other EET regioisomers such as 11,12-EET (66, 67), AA (36,68), and endocannabinoids such as 2-arachidonoylglycerol (37).…”
Section: Hypothesized Mechanisms Involved In Trpv4 Activation By Aa Amentioning
confidence: 99%